1990
DOI: 10.1007/bf00193200
|View full text |Cite
|
Sign up to set email alerts
|

Linkage study of a large family with autosomal dominant polycystic kidney disease with reduced expression

Abstract: We describe a large three generation family with autosomal dominant polycystic kidney disease (PKD). Ultrasonographic screening of 60 family members revealed 20 individuals, whose age ranged from ten to eighty years, with one or several cysts in only one kidney and 7 individuals with cysts in both kidneys. Transmission of unilateral cysts seems to be autosomal dominant, although there are some generation gaps. Linkage studies with several markers of the PKD1 locus on the short arm of chromosome 16 showed no li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The cysts show thickened basement membranes with surrounding interstitial fibrosis, though their epithelia maintain an active capacity for fluid secretion and re-absorption (Chapman et al, 2003;Grantham, 2006). End-stage renal disease (ESRD) occurs in the majority of ADPKD cases (Torres et al, 2007), with approximately 85% of ADPKD cases caused by mutations in PKD1 (Reeders et al, 1985;Pignatelli et al, 1992) and PKD2 mutations account for the remaining 15% (Bachner et al, 1990;Kimberling et al, 1993;Mochizuki et al, 1996). A third locus PKD3 (Daoust et al, 1995), which is likely responsible for a small percentage of ADPKD cases, remains to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The cysts show thickened basement membranes with surrounding interstitial fibrosis, though their epithelia maintain an active capacity for fluid secretion and re-absorption (Chapman et al, 2003;Grantham, 2006). End-stage renal disease (ESRD) occurs in the majority of ADPKD cases (Torres et al, 2007), with approximately 85% of ADPKD cases caused by mutations in PKD1 (Reeders et al, 1985;Pignatelli et al, 1992) and PKD2 mutations account for the remaining 15% (Bachner et al, 1990;Kimberling et al, 1993;Mochizuki et al, 1996). A third locus PKD3 (Daoust et al, 1995), which is likely responsible for a small percentage of ADPKD cases, remains to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…DNA prediction has an added advantage compared to ultrasound screening in being age independent. However, the report of genetic heterogeneity (Kimberling et al 1988;Romeo et al 1988;Brissenden et al 1989;Norby et al 1989;Bachner et al 1990) has made the task difficult for gene carrier detection in ADPKD families. The diagnostic interpretation by genetic linkage may be difficult without knowing the ADPKD type in a particular family.…”
Section: Resultsmentioning
confidence: 94%
“…The disease locus has been shown to link with the alpha-globin gene cluster (Reeders et al 1985(Reeders et al , 1986Lazarou et al 1987) and phosphoglycolate phosphatase (Reeders et al 1986;Watson et al 1987), at a genetic distance of about 5 centiMorgans (cM), by using the highly polymorphic DNA marker 3'HVR. Subsequently, linkage studies in some families have demonstrated genetic heterogeneity (Kimberling et al 1988;Romeo et al 1988;Brissenden et al 1989;Norby et al 1989;Bachner et al 1990) in which the disease gene does not cosegregate with the 16p marker. The mutation causing PKD 1 gene accounts for about 90% in the Caucasian population.…”
Section: Introductionmentioning
confidence: 96%
“…There is a low likelihood (5%) that they had PKD because only 11% of persons at 50% risk before age 30 years have cysts [Bear et al, 1992]. It is possible that each of these patients had a spontaneous mutation for PKD or that there was reduced penetrance of the gene(s) for PKD [Bachner et al, 1991]. PKD is the commonest dominantly inherited renal cystic disorder in humans with a prevalence of about 1 in 1,000 [Iglesias et al, 1983] and a spontaneous mutation rate of 6.5 to 10 ϫ 10 Ϫ5 [Dalgard, 1957].…”
Section: Discussionmentioning
confidence: 93%
“…In about 95% of families with nonsyndromal PKD the gene (PKD1) is linked to 16p13.3 [Reeders et al, 1985]. A second gene locus (PKD4) is found in about 5% of families with the same clinical phenotypes as PKD1 [Kimberling et al, 1988;Bachner et al, 1991;Fossdal et al, 1993]. Linkage has been established to a locus at chromosome 4q13-23 [Kimberling et al, 1993;Peters et al, 1993].…”
Section: Introductionmentioning
confidence: 96%